The Impact Of Employer Branding On Job Performnace: The Mediating Role Of Organizaional Commitment In Thailand (Journal of Namibian Studies : History Politics Culture, 2023)
The objective of this research is to examine the impact of perceived employer branding, organizational commitment and job performance among the employees of jewellery industry in Thailand. To investigate the mediating role of organizational commitment in the connection between perceived employer branding, organizational commitment and job performance on the employees of the jewellery industry in Thailand. This research seeks to gather data from employees of the two generations and holding various positions in the different divisions: Merchandiser, Production and pattern, Sorter, Stone, Designer, and QC in the jewellery business enterprise in Bangkok, Thailand who have agreed to volunteer and participate in this study. Overall, the results of the SEM analysis provide support for the hypothesis that perceived employer branding, organizational commitment, and job performance are all positively correlated.The path coefficient between EB and OC is 0.80, which is statistically significant at the p < 0.01 level. This means that for every one-unit increase in perceived employer branding, there is an 0.80 unit increase in organizational commitment.The path coefficient between EB and JP is 0.40, which is statistically significant at the p < 0.01 level. This means that for every one-unit increase in perceived employer branding, there is a 0.40 unit increase in job performance.The path coefficient between OC and JP is 0.17, which is statistically significant at the p < 0.01 level. This means that for every one-unit increase in organizational commitment, there is a 0.17 unit increase in job performance.The results of the SEM analysis suggest that perceived employer branding is an important factor that can influence organizational commitment and job performance. Organizations that want to improve their employees' commitment and performance should focus on creating a positive employer brand.